Upholding heightened expectations of Indigenous children? Parents do, teachers do not - Peacock, Huw; Prehn, Jacob; Guerzoni, Michael A.; Aitken, Wendy; Andersen, Clair (The Australian Journal of Indigenous Education, 2020)
Abstract This paper argues that a component of increasing the rate of Aboriginal and Torres Strait Islander children and youths completing their secondary education is having parents and teachers maintain heightened expectations of these children in achieving this goal. To understand this phenomenon, we investigate the importance of, and discrepancies between, primary caregiver and teacher outlooks regarding Indigenous youths completing year 12. For the purpose of this paper, we adopt the term ‘primary caregiver’ in place of parent. This is because the majority (87.7%) of P1s analysed are the biological mothers with the remainder being close female relatives. P2s analysed are all male, 93.3% are biological fathers; remainder are step-fathers or adoptive fathers. This paper uses quantitative data from the Longitudinal Study of Indigenous Children to measure expectations from parents and teachers of Indigenous children. Results suggest that parents maintain exceptionally high expectations of their children, while teacher's expectations significantly decline over the course of Indigenous children's primary and secondary schooling years. We suggest that relationships and communication between parents and teachers, regarding expectations of students, are important to establishing an equilibrium in expectations of children, and that teachers may benefit from further training to address any underlying biases towards Indigenous children.